Morphological spatial pattern of peri-urban green infrastructure: a case study of Zhengzhou City, China - Shi, Zhen; Liu, Manshu; Wang, Xinyu; Filepné Kovács, Krisztina (4D Journal of Landscape Architecture and Garden Art, 2025)
Peri-Urban Green Infrastructure (PUGI) possesses significant ecosystem service value yet often remains overlooked. This study employed a composite index and the Jenks natural breaks classification method to identify Peri-Urban Areas (PUAs) in Zhengzhou City, from which PUGI was extracted for morphological spatial pattern analysis (MSPA). The study reveals that the majority of PUAs are situated on the outskirts of urban regions, with a smaller portion located within rural hinterlands. PUGI occupies over half of the land within PUAs, with semi-natural PUGI holding a dominant position, while natural GI primarily serves as connectors. These findings complement theoretical understanding of PUGI’s morphological characteristics and provide insights for planners to optimise PUGI.
Keywords: peri-urban green infrastructure; peri-urban areas; morphological spatial pattern analysis; land use